AB0888 Platelet count in ankylosing spondylitis: can it show the disease activity ?. (12th June 2018) - Rahmouni, S.; Slouma, M.; Dhahri, R.; Metoui, L.; Boussetta, N.; Gueddiche, N.; Laajili, F.; Gharsallah, I.; Louzir, B.
Abstract : Background: C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) are the main inflammatory biomarkers used in assessment of disease activity in numerous inflammatory diseases such as ankylosing spondylitis (SA). In recent years, it has been shown that Platelet count (PC) provided additional information on inflammatory status. Objectives: The present study aimed to investigate the correlation between PC and clinical activity indices assessed by Bath ankylosing spondylitis disease activity index (BASDAI) Methods: The study included 68 patients who fulfilled Assessment of Spondyloarthritis International Society Criteria. A cell blood count, including platelet count, ESR (mm/h), CRP (mg/L) and albumin (g/L), was obtained for each patient. Disease activity measures at the time of blood sampling were obtained using the BASDAI. Statistical Package for Social Sciences (SPSS) was used for analysis. Results: Of the 68 patients, 73.5% were male (Sex Ratio: 2.7). The mean age was 36±12.9 years. The mean disease duration was 40 months [0–192]. The average age of the onset of the disease was 36.6±11.9 years. No patient had ongoing infection at time of study. The mean BASDAI score was 5.1 [1.55–9.2]. Forty-one% of our patients (n=28) had active AS (BASDAI >4) The mean ESR, CRP, albumin and PC were 39.4 (mm/h), 34.1(mg/dL), 39, 32 g/L and 311 (10 3 /mL), respectively. There was a positive correlation between platelet count and following biomarkers: ESR (r: −0.481; p: 0.000), CRP (r: 0.417; p: 0.000) and albumin levels (r: −0.556; p:0.000). A negative correlation between and Haemoglobin (Hg) was noted (r: −0.643; p: 0.000). There was no significant difference in laboratory parameters (ESR, CRP, albumin, PC, Hg) between patients with active AS (BASDAI >4) and those with inactive AS (BASDI <4) patients. Conclusions: Although acute phase reactant such as ESR, CRP and PC mirror disease activity in AS, 1 their values were not associated with disease activity assessed by BASDAI in our study. However, new prospective studies including larger study groups are required to verify the findings of the present study. Reference: [1] Ruof J, Stucki G. Validity aspects of erythrocyte sedimentation rate and C-reactive protein in ankylosing spondylitis: a literature review. J Rheumatol1999;26:966e70. Disclosure of Interest: None declared